2022
DOI: 10.3390/w14071174
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Fishing Vessels on the Heavy Metal Contamination in Sediments: A Case Study of Qianzhen Fishing Port in Southern Taiwan

Abstract: Routine maintenance of fishing vessels and wastewater discharges are primary sources of heavy metals in fishing ports. Sediment pollution assessment is necessary in fishing port management, including sediment dredging and disposal, sewage treatment facility construction, and pollution source control. In this study, sediment heavy metal contents in Qianzhen Fishing Port, the largest pelagic fishery port in Taiwan, were investigated to assess the contamination levels and related potential ecological risks using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 60 publications
0
9
0
2
Order By: Relevance
“…Salinity, pH, and dissolved oxygen (DO) in water samples were determined in situ using the HI 98194 portable meter (Hanna Instruments Inc., Romania). Heavy metals, suspended solids (SS), biochemical oxygen demand (BOD) and ammonia nitrogen (NH 3 ‐N) in water samples, and total nitrogen (TN) and total phosphorous (TP) in sediment samples were determined following the methods in TEPA (2016) and Lim et al (2022). The grain size composition of each sediment sample was analyzed via a laser diffraction particle size analyzer (Beckman Coulter Inc., LS‐230, USA) following the procedures in Lim et al (2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salinity, pH, and dissolved oxygen (DO) in water samples were determined in situ using the HI 98194 portable meter (Hanna Instruments Inc., Romania). Heavy metals, suspended solids (SS), biochemical oxygen demand (BOD) and ammonia nitrogen (NH 3 ‐N) in water samples, and total nitrogen (TN) and total phosphorous (TP) in sediment samples were determined following the methods in TEPA (2016) and Lim et al (2022). The grain size composition of each sediment sample was analyzed via a laser diffraction particle size analyzer (Beckman Coulter Inc., LS‐230, USA) following the procedures in Lim et al (2022).…”
Section: Methodsmentioning
confidence: 99%
“…Heavy metals, suspended solids (SS), biochemical oxygen demand (BOD) and ammonia nitrogen (NH 3 ‐N) in water samples, and total nitrogen (TN) and total phosphorous (TP) in sediment samples were determined following the methods in TEPA (2016) and Lim et al (2022). The grain size composition of each sediment sample was analyzed via a laser diffraction particle size analyzer (Beckman Coulter Inc., LS‐230, USA) following the procedures in Lim et al (2022). The heavy metal concentrations for Hg, Pb, Cd, Cr, As, Cu, Zn, and Ni were analyzed following the protocols described in Chen, Ju, et al (2022) and Chen, Lim, et al (2022) using the inductively coupled plasma optical emission spectrometer (ICP‐OES) (Thermo Scientific Co., iCAP 7400 Duo, USA).…”
Section: Methodsmentioning
confidence: 99%
“…This condition is reflected in the number of facilities that have not been fully utilized. Impacts arising from this condition include damage or inadequate capacity of several facilities, such as land, docks, port ponds, ice factories, clean water availability, and electricity installation infrastructure [5,12,13]. This has resulted in the port function not being carried out optimally and has implications for the reduction of ship visits to fishing ports.…”
Section: Introductionmentioning
confidence: 99%
“…Saha explored different types of GIS spatial interpolation methods, and the final results show that the inverse distance weighting method (IDW) is the optimal interpolation model for studying the spatial distribution pattern of toxic metal content (Saha et al, 2022). Sediment quality guidelines (SQG), pollution load index (PLI), and human health risk assessment have been widely applied to metal ion hazard assessment in various regions (Kolawole et al, 2022;Lim et al, 2022;Mor et al, 2022;Tnoumi et al, 2022;Zhang et al, 2022a). Xu studied the Hulan River Basin and found that Cd has caused serious biological risk in estuarine areas.…”
Section: Introductionmentioning
confidence: 99%